2013
DOI: 10.1161/circulationaha.113.001746
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ /Calmodulin-Dependent Protein Kinase II and Protein Kinase A Differentially Regulate Sarcoplasmic Reticulum Ca 2+ Leak in Human Cardiac Pathology

Abstract: Background— Sarcoplasmic reticulum (SR) Ca 2+ leak through ryanodine receptor type 2 (RyR2) dysfunction is of major pathophysiological relevance in human heart failure (HF); however, mechanisms underlying progressive RyR2 dysregulation from cardiac hypertrophy to HF are still controversial. Methods and Results— We investigated healthy control myocardium (n=5) and myocardium from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
113
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 37 publications
6
113
0
5
Order By: Relevance
“…Interestingly, despite enhanced expression of fetal genes in all phenotypes, p‐phospholamban, S16 was increased in the CR and MILD phenotypes and decreased in the MOD phenotype only. Thus, the MOD phenotype displayed features shown in other studies, where the transition from compensated hypertrophy to overt HF is characterized by increased calcium‐calmodulin‐dependent kinase II activity and decreased PKA phosphorylation of downstream targets leading to increased sarcoplasmic reticulum Ca 2+ leak, reduced sarcoplasmic reticulum Ca 2+ load, and therefore impaired systolic Ca 2+ transients 36. Similarly, the expression of NCX‐1, which is regulated by the mitogen‐activated protein kinases P38 and HDAC,41, 42 and mitochondrial apoptosis markers (Bax and BNIP3), which are regulated by the mitogen‐activated protein kinases JNK,12 were increased in the MOD phenotype only.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, despite enhanced expression of fetal genes in all phenotypes, p‐phospholamban, S16 was increased in the CR and MILD phenotypes and decreased in the MOD phenotype only. Thus, the MOD phenotype displayed features shown in other studies, where the transition from compensated hypertrophy to overt HF is characterized by increased calcium‐calmodulin‐dependent kinase II activity and decreased PKA phosphorylation of downstream targets leading to increased sarcoplasmic reticulum Ca 2+ leak, reduced sarcoplasmic reticulum Ca 2+ load, and therefore impaired systolic Ca 2+ transients 36. Similarly, the expression of NCX‐1, which is regulated by the mitogen‐activated protein kinases P38 and HDAC,41, 42 and mitochondrial apoptosis markers (Bax and BNIP3), which are regulated by the mitogen‐activated protein kinases JNK,12 were increased in the MOD phenotype only.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, in the absence of extracellular calcium, CAP‐induced intracellular Ca 2+ increase was not observed (Figure 1D). Ca 2+ /CaMKII is activated by increased intracellular Ca 2+ concentration, and the CaMKII δ isoform found predominantly in the heart has been shown to play an essential role in cardiac hypertrophy 17. We explored whether CaMKII δ activity and phosphorylation were altered in TRPV1 activation–induced cardiac hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the identification of an exchange protein that was directly activated by cAMP (Epac) further supported the importance of CaMKII-dependent phosphorylation through beta-adrenergic receptor stimulation in the heart [31-33]. Very recently, it has been reported that both CaMKII and PKA functionally regulate RyR but have differential roles in human cardiac pathology [34]. Therefore, abnormal Ca 2+ leak through the RyR may play a significant role in heart failure and may be another promising target of treatment.…”
Section: Discussionmentioning
confidence: 99%